Landslide hazard mapping of Phewa Lake catchment area, Pokhara, central west Nepal - Sikrikar, S. M.; Rimal, L. N.; Jager, S. (Journal of Nepal Geological Society, 1998)
The landslide hazard map of the Phewa Lake catchment area is based on empirical evaluation of the data related to slope instability, obtained through field investigation and various types of geo-scientific maps. The methodology includes making of different types of base maps of various factor that contribute to slope instability of the terrain. Some weighted values are derived for each factor taken into consideration by statistical analysis. According to their significance in slope failure, different numerical values are assigned to each factors. GIS technique is used for integrating all weighted values into final landslide hazard map. By assessing the total weighted values in the final map, the catchment area is divided into high, medium and low hazard zones according to the chances of occurring landslides at specific area. Most of the existing old and active landslides fall within high hazard zone, which indicate the suitability of this method in preparing landslide hazard map.